2022
DOI: 10.3390/ijerph19031635
|View full text |Cite
|
Sign up to set email alerts
|

Through the Second Wave: Analysis of the Psychological and Perceptive Changes in the Italian Population during the COVID-19 Pandemic

Abstract: More than a year has passed since “patient 0” was found and COVID-19 is now an established reality that a lot of people have had to accept and coexist with. In Italy, the pandemic hit in “waves”, but the studies assessing the longitudinal impact of the pandemic in the general population are not many. In this paper, we compared data collected during the first wave with data gathered during the second one, so that we can provide insights about the Italian population’s psychological adaptation to the pandemic als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 54 publications
(59 reference statements)
2
16
0
Order By: Relevance
“…Fear of having serious or irreversible consequences after vaccination may be associated with the fear of death, increasing hesitancy. These results were consistent with other studies in which the main barriers to the COVD-19 vaccine were the perception of limited efficacy, potential adverse effects, and safety concerns [ 51 , 52 , 53 ]. Therefore, the present data suggested that a future information campaign should focus more on reducing the fear of side effects of vaccines than on enhancing their capacity to prevent infection.…”
Section: Discussionsupporting
confidence: 92%
“…Fear of having serious or irreversible consequences after vaccination may be associated with the fear of death, increasing hesitancy. These results were consistent with other studies in which the main barriers to the COVD-19 vaccine were the perception of limited efficacy, potential adverse effects, and safety concerns [ 51 , 52 , 53 ]. Therefore, the present data suggested that a future information campaign should focus more on reducing the fear of side effects of vaccines than on enhancing their capacity to prevent infection.…”
Section: Discussionsupporting
confidence: 92%
“…Several authors (e.g., Guazzini et al., 2022 ) reported an increased risk of mental health problems among the general population in countries around the world in which the rapid spread of COVID-19 forced the government to put in place restrictive measures to limit disease dissemination. The Italian government introduced confinement measures from March 2020 to the beginning of May 2020, including a lockdown, contact restrictions, the closure of educational institutions, and the closure of nonessential workplaces.…”
Section: Introductionmentioning
confidence: 99%
“…However, the vast majority of these studies focused on specific psychiatric symptoms (e.g., anxiety) or included samples with pre-existing mental health problems. Moreover, the vast majority of the studies conducted in Italy – even if very sound from a methodological point of view - included just two waves (e.g., Benfante et al., 2022 ; Guazzini et al., 2022 ; Medda et al., 2022 ). Furthermore, only few studies explored the impact of COVID-19 on the general population by also considering well-being (rather than the mere absence of psychiatric symptoms) on successive time points.…”
Section: Introductionmentioning
confidence: 99%
“…The role of ICTs and more generally of the Internet in emergency scenarios like the pandemic is far from being fully understood. Indeed, the web can offer not only young adults and students an opportunity to cultivate their general sense of belonging but also to receive social support [ 81 , 82 ], which could lead to better adaptation to emergency situations [ 83 , 84 , 85 ]. Future research should also clarify how loneliness varies in remote learning and blended learning conditions outside the current pandemic.…”
Section: Discussionmentioning
confidence: 99%